2013
DOI: 10.1128/mbio.00285-13
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans CUG Mistranslation Is a Mechanism To Create Cell Surface Variation

Abstract: In the human fungal pathogen Candida albicans, the CUG codon is translated 97% of the time as serine and 3% of the time as leucine, which potentially originates an array of proteins resulting from the translation of a single gene. Genes encoding cell surface proteins are enriched in CUG codons; thus, CUG mistranslation may influence the interactions of the organism with the host. To investigate this, we compared a C. albicans strain that misincorporates 28% of leucine at CUGs with a wild-type parental strain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 51 publications
1
71
0
1
Order By: Relevance
“…In the pathogenic yeast Candida albicans an ambiguity in the genetic code results in the systematic miscoding of ∼3% of all Leu codons as Ser. This programmed miscoding event generates an array of proteins originating from a single gene that can be beneficial in some cases, for example by generating increased cell surface variation (37,38). Similar potential mistranslation benefits have been proposed in mammalian and bacterial cells in which errors in protein synthesis have been linked with increased diversity of antigen presentation (4,39,40).…”
Section: Increased Trna Misacylation Provides a Possible Mechanism Tomentioning
confidence: 75%
“…In the pathogenic yeast Candida albicans an ambiguity in the genetic code results in the systematic miscoding of ∼3% of all Leu codons as Ser. This programmed miscoding event generates an array of proteins originating from a single gene that can be beneficial in some cases, for example by generating increased cell surface variation (37,38). Similar potential mistranslation benefits have been proposed in mammalian and bacterial cells in which errors in protein synthesis have been linked with increased diversity of antigen presentation (4,39,40).…”
Section: Increased Trna Misacylation Provides a Possible Mechanism Tomentioning
confidence: 75%
“…This in turn increases phenotypic variationdone of the most important survival skills of C. albicans (Gomes et al, 2007;Miranda et al, 2013). An important example is the variability in cell surface molecules, which is created by CUG mistranslation and which might have a major impact on the fungusehost interaction (Miranda et al, 2013). Taken together, short-and long-term reactions/adaptations to stress or other environmental conditions are regulated by chromosomal changes.…”
Section: The Cug Codon and The Establishment Of Proteome Diversitymentioning
confidence: 99%
“…However, CUG translation is ambiguous, and partial reversion from serine to leucine identity is possible (Gomes et al, 2007), thereby leading to an exponential expansion of the C. albicans proteome. This in turn increases phenotypic variationdone of the most important survival skills of C. albicans (Gomes et al, 2007;Miranda et al, 2013). An important example is the variability in cell surface molecules, which is created by CUG mistranslation and which might have a major impact on the fungusehost interaction (Miranda et al, 2013).…”
Section: The Cug Codon and The Establishment Of Proteome Diversitymentioning
confidence: 99%
“…Altering the ratio of Ser to Leu incorporation at CUG codons introduces diverse cell and colony morphologies, as well as distinct antifungal and immune responses 50,51 . Wild-type C. albicans encodes a CUG-decoding tRNA CAG that is recognized by both SerRS and LeuRS (FIG.…”
Section: Ambiguous Decodingmentioning
confidence: 99%
“…4). Enhanced CUG ambiguity increases cell adhesion by ambiguous translation of adhesins and reduces susceptibility to macrophage killing by decreasing surface exposure of β-glucans 51 . It has also been shown that, in Mycobacterium smegmatis , the level of ambiguous decoding at Asn codons increases during stationary phase and under low pH conditions 52 .…”
Section: Ambiguous Decodingmentioning
confidence: 99%